A Scoping Review of Gut Microbiome and Bifidobacterium Research in Zimbabwe: Implications for Future Studies - Zhou DT; Mudhluli TE; Hall LJ; Manasa J; Munyati S (Pediatric Health, Medicine and Therapeutics, 2023)
Danai T Zhou,1 Taona E Mudhluli,1,2 Lindsay J Hall,3– 5 Justen Manasa,1,6 Shungu Munyati6 1Department of Laboratory Diagnostic and Investigative Sciences, University of Zimbabwe, Harare, Zimbabwe; 2Department of Biochemistry, Midlands State University, Gweru, Zimbabwe; 3Gut Microbes & Health, Quadram Institute Bioscience, Norwich, UK; 4Norwich Medical School, University of East Anglia, Norwich, UK; 5Intestinal Microbiome, Technical University of Munich, Freising, Germany; 6Department of Laboratory Sciences, Biomedical Research and Training Institute, Harare, ZimbabweCorrespondence: Danai T Zhou, Department of Laboratory Diagnostic and Investigative Sciences, University of Zimbabwe, Box A 178, Avondale, Harare, Zimbabwe, Email dzhou@medsch.uz.ac.zw; danaizh@yahoo.co.ukBackground: Gut microbiota play a key role in host health, with certain Bifidobacterium strains critical for immune development. The healthy gut of breastfed infants is dominated by these pioneer microbes, especially the strains that feed on human milk oligosaccharides.Objective: This is a scoping review of gut microbiome research from Zimbabwe. It focuses on distribution and dynamic changes of bifidobacteria, and milk components that promote growth of microbes in infants, together with the distribution of associated gut microbes in adults.Design: Online databases were searched for publications from 2000 to 2023.Results and Analysis: Fourteen publications on microbiota of infants and adults were included in this scoping review. Most were cross-sectional, while three were clinical trials/cohort protocols. Publications focused on pediatrics (78.5%), pregnant women (14.3%), and men (7.2%). Zimbabwe has a high burden of HIV; hence 35.7% of study populations were delineated by HIV status. The laboratory methods used included shotgun metagenomics (62%) or 16S rRNA gene amplicon sequencing. Almost 85% of the studies focused on total microbiome profiles and rarely reported the distribution of different Bifidobacterium species and variants. None of the papers studied human breast milk composition. There were reports of reduced abundance of beneficial genera in pregnant women, children, and adolescents living with HIV. Additionally, gut microbiota was reported to be poorly predictive of child growth and vaccine response, though this was not conclusive.Conclusion: There are few studies that characterize the gut microbiome by Zimbabwe-based researchers. However, studies on strain level diversity of Bifidobacterium and other key microbes, and their role in health during and beyond infancy, lag behind in Zimbabwe and other low- and middle-income countries. Such cohorts are needed to inform future mechanistic studies and downstream translational work such as next-generation probiotics and prebiotics.Keywords: Bifidobacterium, gut microbiome, human milk oligosaccharides, LMIC, prebiotics, probiotics, Zimbabwe